Treatment of a Patient with Fibromyalgia with Ozonized Saline Solution. Case Report (Ozone Therapy Global Journal, 2022)
In Mexico, some studies have indicated that the prevalence of fibromyalgia is 4.8% of the total population and in particular the Hospital de Especialidades del CMN La Raza, about 5% of the consultations of people suffering from chronic pain are due to this cause. Unfortunately, conventional medical therapies aimed at this pathology produce limited benefits. They remain largely pharmacological in nature and tend to treat the symptomatic aspects of various patient-reported disorders. Statistics, however, highlight the fact that 90% of people with fibromyalgia also turn to complementary medicine such as ozone therapy to manage their symptoms. Quality of life has become an indicator of the evolution of the health status of these patients, as an expression of a strategy not only to prolong life, but also to alleviate symptoms and maintain vital functioning.In this work we describe the results of a 69-year-old female with fibromyalgia treated with Ozonated Saline Solution, finding that the results evaluated with visual analog scale (VAS) for pain, sleeplessness and activity, improved up to 90%. The values of CRP 79% and Rheumatoid Factor 50%, showing that the treatment is effective as a complementary treatment in these patients